The choroid plexus acts as an immune cell reservoir and brain entry site in experimental autoimmune encephalomyelitis - Lazarevic, Ivana; Soldati, Sasha; Mapunda, Josephine A.; Rudolph, Henriette; Rosito, Maria; de Oliveira, Alex Cardoso; Enzmann, Gaby; Nishihara, Hideaki; Ishikawa, Hiroshi; Tenenbaum, Tobias; Schroten, Horst; Engelhardt, Britta (Fluids and barriers of the CNS, 2023)
The choroid plexus (ChP) has been suggested as an alternative central nervous system (CNS) entry site for CCR6+ Th17 cells during the initiation of experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis (MS). To advance our understanding of the importance of the ChP in orchestrating CNS immune cell entry during neuroinflammation, we here directly compared the accumulation of CD45+ immune cell subsets in the ChP, the brain and spinal cord at different stages of EAE by flow cytometry. We found that the ChP harbors high numbers of CD45int resident innate but also of CD45hi adaptive immune cell subsets including CCR6+ Th17 cells. With the exception to tissue-resident myeloid cells and B cells, numbers of CD45+ immune cells and specifically of CD4+ T cells increased in the ChP prior to EAE onset and remained elevated while declining in brain and spinal cord during chronic disease. Increased numbers of ChP immune cells preceded their increase in the cerebrospinal fluid (CSF). Th17 but also other CD4+ effector T-cell subsets could migrate from the basolateral to the apical side of the blood-cerebrospinal fluid barrier (BCSFB) in vitro, however, diapedesis of effector Th cells including that of Th17 cells did not require interaction of CCR6 with BCSFB derived CCL20. Our data underscore the important role of the ChP as CNS immune cell entry site in the context of autoimmune neuroinflammation.
Gesehen am 05.07.2023